Trace element determination by ICP-AES and ICP-MS: developments and applications reported during 2006 and 2007 - Linge, Kathryn (Wiley - Blackwell publishing, 2008)
This review describes developments in trace element determination using inductively coupled plasma-atomic emission spectrometry (ICP-AES) and inductively coupled plasma-mass spectrometry (ICP-MS) that were reported in 2006 and 2007. It focuses on the application of ICP techniques to geological and environmental samples; fundamental studies in ICP-MS and ICP-AES instrumentation have largely been ignored. New advances in ICP-MS and ICP-AES were incremental over this period, partly because both techniques are now well-established. A continuing shift towards the hyphenation of low-flow separation techniques has sparked activity in the development of appropriate low-flow interfaces, and papers discussing interference removal also contribute significantly to the volume of research for both ICP-AES and ICP-MS. Whereas the majority of new ICP publications concerned advances in ICP-MS analysis rather than ICP-AES, development for ICP-AES still occurs in almost all areas, particularly in sample introduction and hyphenated techniques.